Class II Malocclusion Treatment by In-House Fabricated, Customized Fixed Functional Appliance in Growing Child - Swati Verma; Falguni Mehta; Mohammad Khursheed Alam; Harshikkumar Arvindbhai Parekh; Valai Kasim Shakeel Ahmed; Chhavi Jain (Case Reports in Dentistry)
Currently, wide arrays of fixed functional appliances are available for the correction of Class II malocclusion. The orthodontist must choose from these appliances depending on the mechanics, efficiency, and cost of the appliance. Fixed functional appliances may reduce the individual visits and hence the cost as compared to the removable appliances. Additionally, it may save the clinician’s chair time. This report discussed the in-house laboratory fabrication and clinical procedure of customized fixed functional appliances by utilizing the readily available dental materials in the orthodontic clinical setting.